2020
DOI: 10.3390/polym12030570
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fructose and Ascorbic Acid on the Performance of Cross-Linked Fish Gelatin Films

Abstract: Gelatin was extracted from fish scales in this work, in an attempt to valorise abundant and available fishery by-products as an approach towards a more circular economy. With this strategy in mind, fish scale gelatin was used to prepare active films. In this regard, the development of advanced materials from gelatin involves its modification to enhance functional properties, particularly barrier properties, to achieve the requirements for specific value-added purposes, such as food or pharmaceutical/biomedical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The ash content was low (Table 4) (0.40-0.65%) and the dry matter content was high, with a moisture content in the range of 8.77-10.44%. Guerrero et al [30] observed that fish gelatine in general contained moisture and ash contents of 8.37 ± 0.35% and 1.06 ± 0.11%, respectively, supporting the observations made in this study. According to the standards recommended for food-grade gelatine by the Gelatine Manufacturers of Europe [31], moisture and ash contents should be limited to ≤15% and ≤2%, respectively.…”
Section: Dry Matter and Ash Contentsupporting
confidence: 92%
“…The ash content was low (Table 4) (0.40-0.65%) and the dry matter content was high, with a moisture content in the range of 8.77-10.44%. Guerrero et al [30] observed that fish gelatine in general contained moisture and ash contents of 8.37 ± 0.35% and 1.06 ± 0.11%, respectively, supporting the observations made in this study. According to the standards recommended for food-grade gelatine by the Gelatine Manufacturers of Europe [31], moisture and ash contents should be limited to ≤15% and ≤2%, respectively.…”
Section: Dry Matter and Ash Contentsupporting
confidence: 92%
“…Protease influences the extraction rate by efficient hydrolysis of the covalent bonds, as well as by disrupting the crosslinks between the molecules of fish collagen (Kouhdasht et al., 2018). Other methods, including nonenzymatic reactions and the addition of ascorbic acid and fructose, resulted in a yield of 13.2 ± 2.3% (Guerrero et al., 2020).…”
Section: Techno‐functional Gap Analysis and Future Directionsmentioning
confidence: 99%
“…Fructose is obtained by using microbial enzymes to hydrolyze the starch extracted from different cereals and transform it into glucose, which, through an isomerization process, is converted to fructose, specifically d -fructose [ 20 ]. Fructose, and generally sugars, can undergo a chemical crosslinking by the so-called non-enzymatic glycation or Maillard reaction [ 21 , 22 ]. Maillard reaction is a chemical and non-enzymatic reaction that is produced in three main steps [ 23 ].…”
Section: Introductionmentioning
confidence: 99%